Performance management - Adeniji, Adeniyi A. (Lagos : Value Analysis Publishers, 2014)
Provides a simplified and pragmatic approach to the understanding of performance management concepts and applications.
Includes bibliographical references.
oif 07/12/2017
Loans
Keywords: Performance--Management; Organizational effectiveness